2015
DOI: 10.4238/2015.october.19.16
|View full text |Cite
|
Sign up to set email alerts
|

MC1R, KIT, IGF2, and NR6A1 as markers for genetic differentiation in Thai native, wild boars, and Duroc and Chinese Meishan pigs

Abstract: ABSTRACT. Mutations in melanocortin 1 receptor (MC1R) gene and v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog (KIT) gene have been shown to affect coat color patterns in pigs. Additional functional marker genes, such as insulin like growth factor-2 (IGF2) and orphan nuclear receptor, germ cell nuclear factor (NR6A1), have been described for variations in factors such as fat deposition, litter size, and vertebra number in pigs. In this study, we investigated 129 pigs representing 4 breeds: Thai i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…In previous studies, the C allele of NR6A1 has appeared in wild boars and in several indigenous pigs, especially Asian pigs (20,22,29). The T allele frequency in Amami-Shimabuta pig was higher compared to other indigenous Asian pigs (23,29). This indicates that the domestication of Amami-Shimabuta is considered to be more advanced than that of the other indigenous Asian pigs examined on the body elongation to increase meat production.…”
Section: Discussionmentioning
confidence: 88%
“…In previous studies, the C allele of NR6A1 has appeared in wild boars and in several indigenous pigs, especially Asian pigs (20,22,29). The T allele frequency in Amami-Shimabuta pig was higher compared to other indigenous Asian pigs (23,29). This indicates that the domestication of Amami-Shimabuta is considered to be more advanced than that of the other indigenous Asian pigs examined on the body elongation to increase meat production.…”
Section: Discussionmentioning
confidence: 88%
“…Mislabeling of species in meat products is most commonly detected by DNA analysis 1 , 2 . For the identification of pork, a number of methods based on polymerase chain reaction (PCR)—restriction fragment length polymorphism (RFLP) has been published 3 5 . Since PCR–RFLP is laborious and time consuming and not applicable to complex food products, it has mainly been replaced by singleplex 6 9 and multiplex real-time PCR assays 10 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Another research piece revealed a mutation in the NR6A1 gene of European pigs, resulting in a change in the binding capacity of the NR6A1 protein and inhibitory proteins that interact with the NR6A1 protein [9]. Furthermore, polymorphisms in the NR6A1 gene in Duroc pigs may affect body length [15]. It was confirmed that NR6A1 is prominently associated with the number of vertebrae in Tongcheng (TC) pigs [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high homology of NR6A1 among different species indicates its potential functional conservation [18]. Based on previous research [8,9,10,11,12,13,14,15,16,17,18], it is rational to hypothesize that the NR6A1 gene may be associated with body size traits of other species. Presently, there is no research regarding the NR6A1 gene in donkeys.…”
Section: Introductionmentioning
confidence: 99%